Penentuan Laju Degradasi Prasarana Irigasi Menggunakan Metode Statistik - Judy Kurniawan; Putu Sudira; Sigit Supadmo Arif (agriTECH, 2008)
Degradation process of irrigation infrastructures is one of the most important things and determines the last result ofAsset Management Planning (AMP). Degradation process will determine irrigation infrastructure’s lifetime, hence, it will influence the whole process of AMP, and finally influence the management of irrigation infrastructures. The objec- tive of this research aims at developing a model of the degradation rate of irrigation infrastructures, as one input for AMP, to support decision making in irrigation infrastructure management. This research was conducted at Sidandang, Pengasih, Jering and Mejing irrigation schemes located at Magelang, Kulonprogo, Sleman, and Bantul Districts, respectively. Statistical model was used to analysis the rate of degradation of irrigation infrastructures.  The model requires the relation between time for degradation and the number of degradations. The data used for analysis was secondary data of asset condition in several years. The result shows that linear model that has been regularly used before is not valid to predict the rate of degradation of irrigation infrastructures based on irrigation facet age. The exponential model was developed in order to find out the more suitable procedure to predict the rate of degradation process based on irrigation facet age, and effective for all types of facet at all types of asset. The rate of degradation process of irrigation asset condition is highly influenced by the rock composition factor and soil physical characteris- tics of asset construction.ABSTRAKProses degradasi prasarana irigasi merupakan salah satu bagian penting dan sangat menentukan hasil akhir perenca-naan manajemen aset (PMA). Hal ini disebabkan karena proses degradasi menentukan umur prasarana irigasi, yang akan mempengaruhi seluruh proses PMA, dan akhirnya juga akan mempengaruhi pengelolaan prasarana irigasi. Penelitian ini bertujuan untuk mengembangkan dan menyusun suatu model laju degradasi prasarana irigasi sebagai salah satu masukan kegiatan PMA untuk mendukung pengambilan keputusan dalam pengelolaan prasarana irigasi. Penelitian dilaksanakan di Daerah Irigasi Sidandang, Pengasih, Jering, dan Mejing, masingmasing terletak di Kabu- paten Magelang, Kulonprogo, Sleman dan Bantul. Metode yang digunakan untuk menganalisis laju degradasi prasa- rana irigasi adalah pemodelan statistik dengan menghitung hubungan variabel waktu yang dibutuhkan untuk setiap proses degradasi dan jumlah kerusakan. Data yang dipergunakan untuk analisis adalah data sekunder kondisi aset irigasi dalam waktu beberapa tahun. Hasil penelitian menunjukkan bahwa model linier yang biasa digunakan selama ini tidak handal untuk memprediksi laju degradasi sarana irigasi berdasarkan umur faset irigasi. Model eksponensial yang dikembangkan lebih handal untuk memprediksi laju degradasi prasarana irigasi berdasarkan umur faset irigasi, dan berlaku untuk semua tipe faset pada semua tipe aset. Proses degradasi kondisi aset irigasi sangat dipengaruhi oleh faktor komposisi batuan dan sifat fisik tanah penyusun aset.